Effectiveness of an Education Program on Nurses' Knowledge and practice toward Radioiodine therapy at Alamal Hospital in Baghdad city - Suhear Jihad, Shahlaa; Mohammed Khudur, Khalida (International Journal of Psychosocial Rehabilitation, 2020)
Radioactive iodine (RAI) is treatment for overactive thyroid and certain types of thyroid cancer. Nurses caring for patients undergoing Radioiodine therapy require specialized knowledge and practice in order to ensure safety for patient's life. so, educational programs concerning this subject can be of imperative benefit for both patient and nurse.Objective: To assess the effectiveness of an educational program on nurses Knowledge and practice toward Radioiodine therapyMethodology: A pre quasi-experimental design (one -group pretest-posttest) was used conducted in this. The present study was carried out at Alamal Hospital in Baghdad Governorate for the period 15th October of 2019 to22th of march 2020. A non-probability (purposive) sample of (30) nurses were selected. questionnaire for knowledge was constructed for the purpose of the study. Validity and reliability of the instrument were determined through a pilot study. Data were analyzed through the use of Statistical package for Social Sciences (SPSS) version. Descriptive and inferential statistical measures were employed.Results: The study indicated that the knowledge and practice scores of participants were inadequate for study group in the pre-test, but the study group knowledge and practice scores have increased after introducing them to the education program. Thus, there were significant differences between study group. The study findings indicate that there are highly significant differences between (pre and post-tests) in the study group regarding nurse's knowledge and practice concerning radioiodine therapy.Conclusion: The study concludes that the effectiveness of an education program concerning radioiodine therapy is positive at a high rate